Trauma Prehospital Hypothermia Prevention and Treatment: An Observational Study. Issue 3 (May 2021) - Mota, Mauro A. L.; Santos, Margarida Reis; Santos, Eduardo J. F.; Henriques, Carla; Matos, Ana; Cunha, Madalena
Abstract : Background: Hypothermia in trauma patients causes increased morbidity and mortality. Swift recognition and treatment are important to prevent any further heat loss. In addition, patient discomfort from cold decreases satisfaction with care. The administration of active and passive rewarming measures is important in the prevention and treatment of hypothermia, but their use in prehospital trauma patients in Portugal has not been previously reported. Objective: To assess the prevalence of hypothermia, the impact of rewarming measures, and the management of the discomfort caused by cold. Methods: This is a prospective cohort study conducted in Immediate Life Support Ambulances in Portugal between March 1, 2019, and April 30, 2020. Results: This study included records of 586 trauma patients; of whom, 66.2% were men. Cranioencephalic trauma was the most common trauma observed, followed by lower limb and thoracic traumas. Mean body temperature increased 0.12 °C between the first and last assessments ( p < .05). Most patients experiencing a level of discomfort of 5 or more on a 0–10 scale reported improvement (from 17.2% to 2.4% after nurses' intervention). Warmed intravenous fluids proved to be effective ( p < .05) in increasing body temperature, and passive rewarming measures were effective in preventing hypothermia. Conclusions: Hypothermia management has to consider the initial temperature, the season, the available rewarming measures, and the objectives to be achieved. The optimization of resources for the monitoring and treatment of hypothermia should be a priority in prehospital assistance. The implementation of rewarming measures improves patients' outcomes and decreases the discomfort caused by cold in prehospital care.